Systematics of alpha-active nuclides and on the validity of the Geiger-Nuttall law - J, Munkhsaikhan; M, Odsuren; G, Khuukhenkhuu (Scientific transaction of the National University of Mongolia. Physics, 2022)
Geiger-Nuttall law, which describes a dependence of the disintegration constant on the range of α-particles, was deduced using the Gamow theory describing the passage of the α-particles through the Coulomb barrier by the quantum mechanical tunneling effect. Ground-to-ground state α-transitions for natural and artificial α-active nuclides were analyzed utilizing the Geiger-Nuttall rule. From rough analysis five group-like branches on the dependence of α-decay half-lives on α-particle energy was observed. Detailed analysis shows that precise linear dependence of the logarithm of α-decay half-lives on the reciprocal of square root of the α-particle energy for even-even isotopes of the U, Pu and Cm there are. However, for some even-even isotopes of the Po, Ra and Th regular behaviour of mass numbers was broken. This non-regularity of the mass numbers on the Geiger-Nuttall line is explained by the nuclear shell model.